SPATIAL DISTRIBUTION OF PLANKTONIC DINOFLAGELLATE IN MAKASSAR WATERS, SOUTH SULAWESI - Abd Saddam Mujib; Ario Damar; Yusli Wardiatno (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
The objectives of this study were to determine the harmful species of dinoflagellates, to determine the concentration of nutriens in surface waters, and to analyze factors affecting the ecological aspects of the harmful dinoflagellates. The results showed that there were 7 genus of dinoflagellates found in this study i.e., Ceratium spp., Gymnodinium sp., Dinophysis sp., Gonyaulax sp., Noctiluca sp., Protoperi-dinium spp., and Peridinium sp. Protoperidinium spp. and Ceratium spp. were the predominant species, with their abundance ranged  of 9-659 cells/L and 6-556 cells/L, respectively.  In temporal scale, values of DO and water light penetration were not significantly different (α>0.05), while for the parameter of nutriens, salinity, and abundance were significantly different (α<0.05). Total abundance of dinoflagellates was significantly correlated with nitrate, nitrite, ammonia, phosphate, salinity, and DO.  Harmful dinoflagellate species such as Dinophysis sp. (DSP), Gymnodinium spp. (NSP and PSP), Noctiluca sp. (anaerobic), and Gonyaulax sp. (anaerobic) were observed in the study area. The high concentration of ammonia (>1 mg/L) in the waters of Losari beach also indicated that the area was affected by anthropogenic activities.   Minimizing nutrient inputs from the land was becoming the most priority measure to be done to avoid such effects related to dinoflagellate harmful algae bloms.Keywords: anthropogenic, dinoflagellates, harmful species, Makassar, nutrients.